Screening of bacterial extracellular xylanase producers with potential for cellulose pulp biobleaching - Isabela da Silva Vasconcelos Rodrigues (Acta Scientiarum. Biological Sciences, 2019)
In this study, two hundred fifty-seven bacterial isolates from a suppressive soil library were screened to study their secretion of alkali-thermostable xylanases for potential use in cellulose pulp biobleaching. Xylanase activity was evaluated in solid and liquid media using xylan as the carbon source. Isolates were initially evaluated for the degradation of xylan in solid media by the congo red test. Selected strains were evaluated in liquid media for enzymatic activity and determination of total protein concentration using a crude protein extract (CPE). An isolate identified as Bacillus species TC-DT13 produced the highest amount of xylanase (1808 U mL-1). The isolate was active and stable at 70°C and pH 9.0, conditions which are necessary for the paper industry. This isolate can grow and produce xylanase in medium containing wheat fiber as a substrate. The CPE of this isolate was used in preliminary testing on cellulose pulp bleaching; enzyme treatment of the pulp resulted in a 5% increase of whiteness.